Globalizacija medicine v 21. stoletju: konferenčni zbornik (University of Maribor Press, 2019)
The Globalization of Medicine in the 21st Century: Conference Proceedings / 28th Conference on Medicine, Law and Society. The contents of the conference book "Medicine, Law and Society - the Globalization of Medicine in the 21st Century" refers to current issues that link medicine and law. Nowadays, artificial intelligence and robots already plan an important role in medicine, however, it is expected to further increase in the future. Although, they are usually linked to precision, consistency and the possibility of a wide field of knowledge, there remain unanswered questions, both medical (e.g. Can a doctor be replaced by a robot?) as well as legal (e.g. Who is responsible for the damage caused by an autonomous robot?) ones. The second set of articles, in the collection, relates to medical, legal, sociological and ethical issues in connection with biomedicine. In their contributions, authors discuss genetic manipulations, legal aspects of reproductive material, personalized medicine … The third part of the collection involves contributions which cover the importance of vaccination in a modern society.